Digital preservation for libraries, archives, and museums - Corrado, Edward M.,Moulaison, Heather Léa (Rowman & Littlefield, 2014)
What is digital preservation? – Getting started with the digital preservation triad – The OAIS reference model – Human resources and education – Sustainable digital preservation – The digital preservation repository and trust – Metadata and metadata for digital preservation – File formats and software for digital preservation – Collection development – Preserving research data – Preserving humanities content
Literaturverzeichnis
Keywords: Digital preservation; Preservation metadata; Electronic information resources